Teaching Styles and Teaching Performance of the Faculty of A University in Cebu City: Basis for A Faculty Development Program - Narsico, Lalaine O.; Narsico, Peter G.; Polinar, Mark Anthony N. (Future Science / FSH-PH Publications, 2023)
Teachers must be relevant in their teaching style to respond effectively to the challenges brought about by environmental changes. This study measured how well the teachers could utilize various styles and methods to create meaningful teaching-learning experiences. This study determined the gap between the full use of styles, methods, and the current practices in the university in Cebu City to bridge the current practices with what is perceived to be ideal. The research design made use of the quantitative method. Using a stratified sampling technique, the data were collected from 2,683 respondents through questionnaires for teaching styles and teaching performance. The respondents came in three clusters: namely, teachers, students, and administrators in six colleges. Based on the findings, the various teaching styles ranged from being practiced often to being always practiced, and their teaching performance ranged from very good to excellent. A seminar-workshop was proposed to improve the areas of teaching styles and teaching performance with the lowest ratings. In the seminar, teachers will be introduced to the core principles related to the topics and will engage in activities designed for principle integration in actual classroom situations. Furthermore, periodic 360-degree performance evaluations shall be conducted to ensure adherence and compliance with the agreed core principles.